An analysis of the results after five years of implementation of the new educational program for teachers of english plan MINED at four universities of San Salvador 1998 - 2002. - Alvarado Ayala, María Guadalupe; Romero Rivera, José Efraín (2024)
During the teachingـ learning process a lot of circumstances take place that can help or block that process, which will affect the achievement of the educational objectives. For this reason, it is a must for teachers to make their best effort so that their work in class can be effective. Teaching is a complex process that can be conceptualized in many ways. Traditionally, language teaching has been described in terms of the actions and behaviors that teachers carry out in the classroom and their effects on students. For this reason, a teacher of English needs to have a pedagogical, didactical, and methodological competence, as well as an advanced knowledge of the specialized area of the language he∕she is teaching. To fulfill all the duties related with the specialized area of English, a teacher must possess an advanced domain of the four macro skills of that language: listening, speaking, reading, and writing. In addition, he∕she must have some fundamentals of grammatical and linguistic aspects of it. For attaining this, the University of El Salvador and other institutions of higher education have programs for training teachers of English that included five or six courses to develop the four macro skill of the language, as well as other courses about English Grammar and Linguistics. However, in 1998, The Ministry of Education of El Salvador implemented a new curriculum that regulates all the training programs for teachers, which had to be adopted by all institutions that serve those programs (Art. 57, Law of Higher Education of El Salvador), this program did not include the English courses that were present in the former plan; instead, it had other courses about pedagogical and methodological aspects, including five teaching practice courses. For this reason MINED established new academic requirements in order to be accepted as a student of this new English teaching program. In order to analyze the impact of these new requirements on students taking the new educational program for teachers of English with regard to the results after five years of implementation, two undergraduates of “Licenciatura en Inglès” of the University of El Salvador carried out this essay at four universities of San Salvador that offer this program.